2019
DOI: 10.1007/s13197-019-03640-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding carob molasses on physical and nutritional quality parameters of sesame paste

Abstract: This study focused on the formulation of food products, based on sesame and carob. The possibility of developing blends from sesame paste and carob molasses, using molasses concentrations of 30, 40 and 50%, at 60, 70 and 80°Brix, respectively, has been studied. The blend prepared with 50% carob molasses at 60°Brix was found to be the most acceptable product, according to a sensory acceptability test. Sesame paste, supplemented with carob molasses, was evaluated for physical quality (oil separation, colour and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
1
16
0
1
Order By: Relevance
“…The addition of carob syrups (TSC 33%) to sesame paste (TSC 1.17%) (ratio 1:1) for the elaboration of carob creams significantly increased the sugar content in the formulated blend (TSC approx. 10%) [29]. However, the value was lower than expected, probably due to the formation of a stable emulsion between the sugar and fat molecules present in the blend.…”
Section: Simple Carbohydrates or Sugarsmentioning
confidence: 70%
See 3 more Smart Citations
“…The addition of carob syrups (TSC 33%) to sesame paste (TSC 1.17%) (ratio 1:1) for the elaboration of carob creams significantly increased the sugar content in the formulated blend (TSC approx. 10%) [29]. However, the value was lower than expected, probably due to the formation of a stable emulsion between the sugar and fat molecules present in the blend.…”
Section: Simple Carbohydrates or Sugarsmentioning
confidence: 70%
“…In the same way, several works showed increases in the content of phenolics after the addition of carob pulp flour in cream recipes [29,30]. Furthermore, comparing raw materials in cream elaboration, Racolta et al [31] found that the cocoa prototype displayed the highest content of polyphenols (929 mg GAE/100 g), followed by the carob prototype (844 mg GAE/100 g), and, as expected, the control (sunflower kernel) sample had the lowest value (749.80 mg GAE/100 g).…”
Section: Phenolic Contentmentioning
confidence: 73%
See 2 more Smart Citations
“…On the market's shelves, carob products are exposed with wide varieties including: powder, creams and molasses. Carob molasses with tahini is the Lebanese sweets signature (Tounsi, Kchaou, Chaker, Bredai, & Kechaou, 2019). Molasses is produced from sugar rich fruit juices by boiling until achieving 70%-80% soluble dry matter content (Akbulut & Özcan, 2008).…”
Section: Introductionmentioning
confidence: 99%